Facilitating Strategic Operations by Making Use of a Model Incorporating a Stochastic Integral - Artikis, Constantinos T.; Artikis, Panagiotis T. (Communications in Mathematics and Applications, 2019)
Formulation, investigation, and practical interpretation of stochastic models are generally recognized as extremely useful research activities for a wide class of scientific disciplines. The paper makes use of a stochastic integral and a product of two positive random variables for formulating a stochastic model. A characterization and an interpretation in strategic operations arising in financial economics of the formulated stochastic model are also established by the paper.